Unusual combination of gestational trophoblastic neoplasias: case report - Ramilo,Irina Dulce Tapadinhas Matos (2014)
Gestational trophoblastic disease comprises a heterogeneous group of lesions arising from abnormal proliferation of trophoblastic cells. An elevation of human chorionic gonadotropin after evacuation of a molar pregnancy should suggest the hypothesis of a persistent gestational trophoblastic neoplasia. We present a rare case of coexistence of choriocarcinoma and placental-site trophoblastic tumor in the same tumor, whose diagnosis was made based on the correlation of morphological, microscopic and immunocytochemical studies, due to the difficulty in diagnosing these mixed tumors based on conventional histology only.